IMPLEMENTATION OF THE ENFORCEMENT OF DISCIPLINES FOR PRISONERS OF LAW VIOLATERS IN CLASS IIA CIKARANG COMMUNITY INSTITUTIONS - Dwiyana, Renovan; Yuska, Syahrial (Journal of Management Small and Medium Enterprises (SMEs), 2025)
This research examines how the enforcement of disciplinary punishments for inmates who violate discipline is implemented in Class IIA Cikarang Prison. Prisons not only function as a place to serve sentences, but also aim to foster, rehabilitate, and resocialize inmates. Enforcement of discipline against violators of discipline is the key to maintaining order and security in the Prison. This research found that discipline enforcement has been carried out in accordance with the rules set out in Law No. 22 of 2022 concerning Corrections and Regulation of the Minister of Law and Human Rights No. 8 Year 2024 about Prison Discipline. The process involves supervision by officers, reporting violations, and trial by the Correctional Observer Team (TPP), who determines the punishment. The regular organizational structure of the Prison also helps coordination between officers in carrying out the enforcement of this discipline. Research uses qualitative methods with a descriptive approach, collecting data through observation, interviews, documentation, and literature studies. The goal is to provide a complete picture of how discipline is enforced in Class IIA Cikarang Prison. Keywords: Implementation; Disciplinary Punishment; Prisoners; Offenders